Minimalisasi Kecemasan pada Ibu Hamil dengan Kartu Pintar Samas (Sadar Kecemasan) - Eka Widyastuti, Deny; Ernawati; Megayana Yessy M; Arista Apriani (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2024)
Maternal mental health has become a concern of the international community. Many women experience mental health disorders during and after pregnancy which often do not receive more attention and are considered normal. Anxiety that arises in pregnant women must be handled properly because this has an impact on the mother's mental health. The effects of poor mental health include the incidence of premature birth, low birth weight, early neonatal complications, neurodevelopmental problems in childhood aged 3-5 years and mental health and behavioral problems in adolescents. This community service is carried out with the aim of increasing maternal awareness about anxiety in pregnant women using the Samas smart card (Anxiety Awareness). The method used in this community service is using lecture and independent methods. After being given the SAMAS (Anxiety Awareness) smart card, all pregnant women were able to explain the meaning of anxiety, risk factors for anxiety, causes of anxiety, symptoms of anxiety, prevention of anxiety and the consequences of anxiety. It is hoped that this activity can be utilized by midwives both in PMB and in villages and also by cadres in providing health education regarding anxiety in pregnancy.   ABSTRAK                 Kesehatan mental ibu sudah menjadi perhatian masyarakat internasional. Banyak wanita mengalami gangguan kesehatan mental selama dan setelah kehamilan yang seringkali tidak mendapatkan perhatian lebih dan dianggap hal yang biasa. Kecemasan yang muncul pada ibu hamil harus diatasi dengan baik karena hal ini berdampak pada kesehatan mental ibu. Efek dari kesehatan mental yang buruk antara lain kejadian persalinan prematur, berat badan lahir rendah, komplikasi neonatal dini, masalah perkembangan saraf masa kanak-kanak usia 3-5 tahun dan masalah kesehatan mental dan perilaku remaja. Pengabdian kepada masyarakat ini dilakukan dengan tujuan untuk meningkatkan kesadaran ibu tentang kecemasan pada ibu hamil menggunakan kartu pintar samas (Sadar Kecemasan). Metode yang digunakan dalam pengabdian masyarakat ini adalah menggunakan metode ceramah dan mandiri. Setelah diberikan kartu pintar SAMAS (Sadar Kecemasan) seluruh ibu hamil sudah dapat menjelaskan mengenai pengertian kecemasan, faktor resiko kecemasan, penyebab kecemasan, gejala kecemasan, pencegahan kecemasan dan akibat dari kecemasan. Kegiatan ini diharapkan dapat dimanfaatkan baik oleh bidan baik di PMB maupun di desa  dan juga oleh kader dalam memberikan pendidikan kesehatan mengenai kecemasan pada kehamilan.